1988
DOI: 10.1111/j.1423-0410.1988.tb04682.x
|View full text |Cite
|
Sign up to set email alerts
|

Complement‐Independent Lysis of Human Red Blood Cells by Cold Hemagglutinins

Abstract: Hemolysis mediated by human antibodies is generally ascribed to the attack of red blood cells (RBC) by complement. We here extend earlier in vitro observations which indicate that potent cold agglutinins can directly cause lysis of RBC without the participation of complement. We have noted that EDTA plasma taken from patients with cold agglutinin disease is frequently reddish if the plasma is not immediately separated from the cells at 37 degrees C. Moreover, eluates prepared in such cases from plasma or heat-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…We found that CAD samples induced some lysis of hRBCs, even in the presence of 10 mM EDTA, suggesting that in vitro sensitization of hRBCs in CAD plasma induced some complement-independent lysis. 18 However, of the 40 CAD samples tested, only plasma from patient 5 (P5), the sample found to contain the highest titers of CAs at both 4°C and 24°C (supplemental Table 1), exhibited significant EDTA-dependent hemolysis. In a concentration-dependent manner, TNT003 completely inhibited complement-dependent lysis of P5-sensitized hRBCs with an IC 50 of 5.1 mg/mL (34 nM; Figure 4A).…”
Section: Tnt003 Inhibition Of Ca-mediated Hemolysis and Anaphylatoxinmentioning
confidence: 99%
“…We found that CAD samples induced some lysis of hRBCs, even in the presence of 10 mM EDTA, suggesting that in vitro sensitization of hRBCs in CAD plasma induced some complement-independent lysis. 18 However, of the 40 CAD samples tested, only plasma from patient 5 (P5), the sample found to contain the highest titers of CAs at both 4°C and 24°C (supplemental Table 1), exhibited significant EDTA-dependent hemolysis. In a concentration-dependent manner, TNT003 completely inhibited complement-dependent lysis of P5-sensitized hRBCs with an IC 50 of 5.1 mg/mL (34 nM; Figure 4A).…”
Section: Tnt003 Inhibition Of Ca-mediated Hemolysis and Anaphylatoxinmentioning
confidence: 99%
“…A propor tion of these cells are phagocytosed, whereas the majority of the cells are released from temporary RES sequestra tion in the liver after cleavage of C3b by factor I as C3dg-coated erythrocytes with an obviously normal life span [9,10], Furthermore, after recirculation of C3dg-coated erythrocytes, these cells seem to be more resistant to fur ther complement fixation by CA, which can be considered as a protective mechanism [3,5,11]. There are, however, reports which indicate that CA with anti-I specificity may -probably by increase of membrane fragility -induce lysis of RBC without the action of complement [12], In the past, most studies in this field have been attribut ed to CA directed against I antigen. With the better understanding of the variety of CA specificities and the characterization of the appropriate antigens we wanted to extend the investigation on CA-induced complement-me diated reactions.…”
Section: Introductionmentioning
confidence: 99%